ANALISIS GEGAR BUDAYA DALAM KONTEN YOUTUBE TOMCHU “CULTURE SHOCK! ORANG KOREA KAGET TINGGAL DI INDONESIA KARENA…” - Dea Stepani Surbakti; Kristina Damai Yanti Simorangkir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Foreign speakers who are visiting Indonesia and the reaction given by them when looking at various phenomena or habits that Indonesian people do not exist in their country, but in Indonesia it is very common, and lifting myths that legend among Indonesian people. This research aims to analyze culture shock in YouTube Tomchu content, Korean people are surprised to live in Indonesia. This research is important to study as it will be beneficial for individuals around the world to know the cultural adjustment processes that occur in their new cultural environment and will examine the cultural concussions experienced by Koreans living in Indonesia. This research is a qualitative descriptive study. Researchers used indicators based on Ward's theory of concussion. The results of the analysis showed that the foreign speaker had lived in Indonesia for 2 months and experienced a cultural concussion on the culture and customs of Indonesian people who were very different from their country. One Korean citizen said most Koreans living in Indonesia are used to spray gun instead of tissue because they feel hygienic. There are no 4 seasons in Indonesia. But in Indonesia there is also one of the hot areas such as summer in Korea, namely Tangerang and Bekasi. And in Indonesia there are also drivers and maids. One Korean citizen said he was surprised to live in Indonesia.